Discourse Analysis of journalistic discourse: The Approach to Critical discourse analysis of speech in the Saudi Press - Alotebi, Tahini Sahel (Journal of Humanities & Social Sciences, 2019)
This study, which entitled "Discourse Analysis of journalistic discourse: The Approach to Critical discourse analysis of speech in the Saudi Press", comes in the context of investing discourse analysis through its critical linguistic approach to the approach of the texts of the Saudi newspapers through different press types. In addressing the problem of research, the study adopted the method used by (Fairclough, N) for his critical approach to speech analysis, considering that this approach considers the press discourse to be the media activity that reflects the general view of the community structure and the outcome of this historical, political and cultural society. The importance of the study is to link linguistic analysis with social analysis, through language analysis as it relates to the social context in which it is used and the social conditions surrounding its use. This study aims at revealing the levels of journalistic analysis in the Saudi newspapers, based on the three-level approach: analysis at the textual level, the level of discursive (rhetorical) practices, and the level of social practices. The textual level includes: the detection of the linguistic choices underlying the naming and referral strategy, the coping strategy, and the strategy of adaptation and necessity, and in rhetorical practices, ie, the production, distribution and consumption of text, including the study of linguistic style. As well as addressing the issue of compatibility within and outside the text in the press. Social practices include the study of the external influences that make up the production and consumption of the press in examining the practices of the three types of newspapers: in terms of their economic, political and ideological practices. The results of this study reveal the effect of textual tools on the identification of the explicit and implicit meanings conveyed by these words and the selected structures. In the rhetorical practices, it reveals the external influences that formed the production and consumption of the news, and also formed and formulated the production and consumption of other texts. It has revealed the relationship of social media practices in their ideological